Effectiveness and tolerability of second-line therapy with vildagliptin versus other oral agents in type 2 diabetes (EDGE): post-hoc subanalysis of the Belgian data. Issue 3 (June 2014) - Hoste, J.; Daci, E.; Mathieu, C.
<x content-type="archive" xml:space="preserve">Abstract</x> Aim: To assess the efficacy and safety of vildagliptin versus other oral glucose-lowering drugs added to antidiabetic monotherapy in Belgian patients with type 2 diabetes mellitus, in comparison to the global EDGE study results. Methods: This is a pre-specified post-hoc subanalysis of the Belgian patient cohort from a worldwide 1-year observational study that compared the effectiveness and tolerability of vildagliptin to other oral antidiabetic agents in type 2 diabetes patients failing monotherapy with oral glucose-lowering agents (EDGE). A total of 1793 Belgian patients were enrolled. Physicians could add any oral antidiabetic drug and patients entered either into the vildagliptin or the comparator cohort. The primary effectiveness and tolerability endpoint was defined as the proportion of patients having a treatment response (HbA1c reduction from baseline to month 12 endpoint >0·3%) without hypoglycemia, weight gain, peripheral oedema, or gastrointestinal side-effects. Results: In the Belgian population, 37·8% of patients in the vildagliptin group and 32·8% in the comparator group had a decrease in HbA1c of >0·3% without the predefined tolerability issues of hypoglycemia, weight gain, oedema or, gastrointestinal complaints (primary endpoint), resulting in an unadjusted odds ratio of 1·24 (95% CI: 0·96–1·61). Mean HbA1c change from baseline was −0·81% in the vildagliptin cohort and −0·75% in the comparator cohort. Overall, vildagliptin was well tolerated with similarly low incidences of total adverse events (14·9% versus 14·5% in the compactor group) and serious adverse events (2·7% versus 2·5% in the comparator group). Conclusion: In this EDGE subgroup of Belgian patients with type 2 diabetes who do not achieve the glycemic targets with monotherapy, a similar trend as in the global EDGE study was observed. Adding vildagliptin as a second oral glucose-lowering agent resulted in lowering HbA1c to <7% without weight gain, hypoglycemia or peripheral oedema in a higher proportion of patients than comparator oral antidiabetic drugs, with no differences in the reported number of adverse events.